Ethnocentrism and ethno-political conflicts in Northern Nigeria: A critical analysis - Wunti, Musa Adamu; Moniruzzaman, Md. (International Institute of Academic Research and Development (IIARD), 2016)
Nigeria is a hotspot for numerous conflicts, especially in the postcolonial times. These intractable conflicts include ethnic, religious, political, sectarian, communal, Settlers-Natives and Pastoralist-Farmers dimensions. On this occasion, different scholarly arguments were advanced to know whether there is a generalizable cause for the menace. Much of these studies focus on conflicts associated with federal structure, uneven development, resources control and marginalization explaining the wider context of the problem. This article explores the significance of understanding the historical context of ethno-political conflict in Northern Nigeria and examines why conflicts keep reoccurring between different communities in the region. The article also assumes that, it is significant to note the influence of politicization of ethnicity, selective injustice and elite manipulation in conflict analysis in Nigeria. It concludes that ethno-political conflicts in Nigeria are fundamentally influenced by bad politics and bad governance. Therefore its management has become a mirage in spite of series of interventions to put the conflicts to an end.